To find the inverse, we:
• change f(x) to y
,
• interchange x and y
,
• solve for y
Thus,
![\begin{gathered} f(x)=2x^2-5 \\ y=2x^2-5 \\ x=2y^2-5 \\ 2y^2=x+5 \\ y^2=(x+5)/(2) \\ y=\pm\sqrt[]{(x+5)/(2)} \\ f^(-1)(x)=-\sqrt[]{(x+5)/(2)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2uylp7mv6w9duvm0sh8yqq1l9ttxmvly41.png)
We take the "negative" part of the function since it is defined for - ♾ < x < 0.
We found inverse of f.
Now, to find f^(-1) (-2), we put -2 into the inverse and evaluate.
![\begin{gathered} f^(-1)(x)=-\sqrt[]{(x+5)/(2)} \\ f^(-1)(-2)=-\sqrt[]{(-2+5)/(2)} \\ =-\sqrt[]{(3)/(2)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dca67d1078l7r8eo60jn1s6205o1jjobeq.png)